PERAN PENDIDIKAN TINGGI DALAM MENGEMBANGKAN SENI GRAFIS DI INDONESIA - Damayanti, Nuning Y (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
Conventional Graphic Art is understood by academics through the history of its development.The Chinese nation is thought to have started the tradition of print as the forerunner of graphicart in its 'primitive' era, while the Romans began etching-glass techniques for portraying gladiators.Furthermore, the Japanese in the 8th century had begun their first authentic print by tracing andprinting Buddhist faces. When the Europeans used it as a printing technique as a medium forartistic expression, the word